Bounded solutions for fuzzy integral equations of fractional order - Wang, Haihua (Advances in difference equations, 2018)
In this paper, we consider sufficient conditions for the boundedness of every solution of fractional order fuzzy integral equations. Some examples are given to illustrate our results.